Myths, meaning making, and mass media - Nass, Colin Wayne (Rhodes University, 2026)
This study investigates the convergence of conspiracy theories and alternative spirituality on 4chan’s /pol/ board, with a focus on antivaccination narratives during the COVID-19 pandemic. Contextualised within the digital ethnography framework, the research explores the unique cultural dynamics of /pol/, a space characterised by anonymity, ideological extremism, and rapid dissemination of user-generated content. Detailed exposition of the development of digital communities with its similarities and differences from how traditional communities formed was central to situating the study in the current literature on conspiracy theories in the digital age. Coupled with how narratives constitute interpretations of reality, the study used conspiracy theories and stigmatised knowledge as a means to investigate the attractiveness and, perhaps, necessity of fringe ideas to answer difficult questions and ease psychological strain. Through thematic analysis of forum threads, this research examines how users construct and propagate "conspirituality"—a hybrid worldview combining conspiratorial ideation with New Age spirituality. Key findings reveal that this space facilitates the memetic evolution of narratives portraying vaccination as a mechanism of global control, often intersecting with antisemitic and apocalyptic religious frameworks. These conspiratorial narratives were found to form the basis for strong community connections that helped individuals feel part of a larger group and resulted in in-/outgroup violence. The study contributes to media studies by offering insights into the mechanics of online narrative formation, the role of digital platforms in amplifying fringe ideologies, and the socio-political implications of these dynamics in a hyperconnected world. It underscores the need for critical engagement with digital cultures to understand their broader societal impact and gives insight into the social movements that form from the bricolage of beliefs used to construct such narratives and ideologies.
a digital ethnography of anti-vax conspirituality on 4chan’s /pol
Keywords: Uncatalogued